Les médiations sociales, culturelles et technologiques dans la production et l’appropriation des intergiciels de l’industrie du jeu vidéo au Canada - Damien Charrieras (Communication)
The industrial sector of game middleware is bound up with the development of video game industries. Canada is at the forefront of those sectors whose economical importance is growing. In his study of the role of these game middleware industries in the production process of a video game, the author focuses on the game middleware circulation to assess the multiple relationships between middleware industries, video game developers in Canada and the communities of developers participating in the evolution of these technologies.